Design and Development of an Integrated Futsal Court Scheduling Reservation Information System in Subang Regency Using the Greedy Algorithm - Wijaya, Masesa Angga; Iqbal, Mohammad; Putra, Febriandika (Marqcha Institute, 2025)
The futsal court reservation system in Subang Regency is still conducted manually, leading to several issues. From the renters' perspective, it is difficult to schedule futsal courts, and they must visit the futsal venue in person to make a reservation. From the court managers’ perspective, the manual recording process results in paper waste due to the use of notebooks, and there are frequent incidents of lost payment receipts and scheduling data. The system development method used is the System Development Life Cycle (SDLC), applying the waterfall model which includes the stages of planning, analysis, design, and system implementation to ensure a structured, tested, and measurable system that meets user needs effectively. To optimize scheduling recommendations, this system utilizes the greedy algorithm, which can provide alternative suggestions when the desired court is unavailable at the requested time. These recommendations are based on the nearest available times and aim to provide the best solution for renters. This study produces an information system designed to facilitate the reservation and scheduling process of futsal courts in Subang Regency. The system is designed for renters to make futsal court reservations and for managers to manage and record reservation data. In addition, the study implements the greedy algorithm to optimize scheduling recommendations when the desired court is fully booked. The system has been tested using Black Box Testing and functions correctly with 100% valid results, and the User Acceptance Testing (UAT) measurement yielded an 86% satisfaction rate, indicating that the futsal court scheduling reservation information system works well and is feasible for use.